Stability of Four Commercial Microbial Phytase Sources Under Increasing Conditioning Temperatures and Conditioner Retention Times During Pelleting - C. N. Truelock; A. D. Yoder; C. E. Evans; C. R. Stark; S. S. Dritz; J. W. Wilson; N. E. Ward; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2018)
This experiment was designed to evaluate the effects of conditioning temperature and retention time on the stability of 4 commercially available microbial phytases in a corn soybean meal diet. Treatments were arranged in a 4 × 3 × 2 factorial of phytase source (A, B, C, and D), conditioning temperature (180, 190, and 200°F), and conditioner retention time (30 and 60 s). Diets were formulated to release 0.15% phosphorus. A total of 5 mash samples from each treatment were analyzed for phytase. Diets were pelleted via steam conditioning (10 × 55 in. Wenger twin staff pre-conditioner, Model 150) using a 30-horsepower pellet mill (1012-2 HD Master Model, California Pellet Mill) with a 3/16 × 2 in. pellet die. Production rate was set at 10 lb/min, approximately 30% of the rated throughput for the pellet mill. All treatments were replicated on 3 separate days. Retention time was randomized within day and phytase sources were randomized within retention time. Pellets were collected after the die and cooled for 10 min. Five cooled pellet samples per treatment per day were analyzed for phytase. Data were analyzed using the GLIMMIX procedure in SAS 9.4, with pelleting run as the experimental unit and day as the blocking factor. There was no evidence for a source × conditioning temperature × retention time interaction for hot pellet temperature or phytase stability. Increasing conditioning temperature (180, 190, and 200°F) increased (quadratic,P<0.03) hot pellet temperature (203, 208, and 211°F, respectively). There was no evidence of difference in hot pellet temperature due to retention time. There was a phytase source × conditioning temperature interaction (P= 0.01) for phytase stability. At conditioning temperatures of 180, 190, and 200°F, phytase stabilities were 33.7, 17.5, and 16.3% for A; 13.0, 8.3, and 9.0% for B; 24.2, 11.2, and 11.8% for C; and 20.7, 11.5, and 9.7% for D; respectively. At conditioning temperatures of 180 and 190°F, phytase A had greater (P<0.05) stability compared to all other sources. At 200°F, there was no evidence of difference between phytase A and C stability, but stability of phytase A was greater (P<0.05) than phytase B and D. Phytase stability of B was less (P<0.05) than that of the other sources when pelleted at 180°F. When pelleted at a conditioning temperature of 200°F, phytase stability was similar between phytase B, C, and D. There was no evidence of difference in phytase stability due to retention time. Microbial phytase stability was reduced by increasing conditioning temperature, although the amount of reduction was dependent on phytase source. Additionally, a maximum phytase stability of 33% was observed with the equipment used in this study, indicating severe consequences of achieving hot pellet temperatures above 200°F.
Keywords: conditioner temperature; pelleting; phytase stability; retention time